2021
DOI: 10.3389/fneur.2020.586610
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Phenotyping and Biomarkers in Spinal and Bulbar Muscular Atrophy

Abstract: Background: Spinal and bulbar muscular atrophy (SBMA) or Kennedy disease [OMIM: 313200] is a rare X-linked neuromuscular disease. Patients commonly present with muscle cramps, tremors, leg weakness, dysarthria and dysphagia.Methods: We deeply phenotyped and evaluated the possible extent of affected systems in all patients with SBMA in Latvia (n = 5). In addition, neurophysiological studies and blood analyses were used to perform a molecular diagnosis and evaluate biochemical values. We analyzed neurofilament l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
(54 reference statements)
1
5
0
1
Order By: Relevance
“…13 Previous studies showed that non-specific features like cramps, myalgia and fatigue precede the appearance of motor symptoms. 6,7 However, all of our patients most commonly had motor symptoms at the onset along with non-specific symptoms. Early prominent hand tremor was noted in five patients, with initial diagnosis as essential tremors in one patient (P6).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…13 Previous studies showed that non-specific features like cramps, myalgia and fatigue precede the appearance of motor symptoms. 6,7 However, all of our patients most commonly had motor symptoms at the onset along with non-specific symptoms. Early prominent hand tremor was noted in five patients, with initial diagnosis as essential tremors in one patient (P6).…”
Section: Discussionmentioning
confidence: 74%
“…Other non-specific symptoms, such as muscle cramps, myalgia, excessive fatigability and postural hand tremors, tend to occur earlier than the typical motor features. 6,7 KD is a multisystem disorder with metabolic derangements, such as impaired glucose tolerance, dyslipidemia, thyroid dysfunction, gynaecomastia, erectile dysfunction and loss of libido. 8 Prevalence of KD is unknown in India due to its rarity, lack of awareness among neurologists and its overlapping features with amyotrophic lateral sclerosis (ALS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spinal and bulbar muscular atrophy or Kennedy disease, a rare X-linked neuromuscular disease caused by a CAG repeat expansion in the first exon of the androgen receptor gene, is manifested by bulbar symptoms, muscle cramps, leg weakness, and tremor ( 173 ). The patients have evidence of small or large nerve fiber neuropathy and, therefore, the observed tremor may be a neuropathic tremor.…”
Section: Other Rare Forms Of Tremormentioning
confidence: 99%
“…La atrofia muscular espinal y bulbar o enfermedad de Kennedy, una rara enfermedad neuromuscular ligada al cromosoma X causada por una expansión repetida de CAG en el primer exón del gen del recTPEor de andrógenos, se manifiesta por síntomas bulbares, calambres musculares, debilidad en las piernas y temblores ( 173 ). Los pacientes tienen evidencia de neuropatía de fibra nerviosa pequeña o grande y, por lo tanto, el temblor observado puede ser un temblor neuropático.…”
Section: Otras Formas Genéticas De Temblorunclassified